Fraude ao Mercado de Capitais e a responsabilidade civil objetiva da companhia perante os seus Investidores - Abreu, Alex de Souza (2022)
The Brazilian legal system, especially Law n. 6,385, December 7, 1976 (Capital Market Law), the Corporate Law (LSA) and regulations of the Securities and Exchange Commission (CVM), although they have a complex system of accountability for illegal acts, do not provide for accountability company in relation to investors. The objective of this study is to verify the limits of damages in relation to the company versus a shareholder or a third part; analyze the spectrum of direct and indirect damages; and understand if there are and what elements are necessary to verify these damages and can also be directly affected. The methodology to be used in this study is deductive, through a bibliographic and documentary approach, by reading works, scientific articles, dissertations and theses on the subject, as well as the revision of the legislation that applies to the subject. The study brings as results and conclusions that without excluding the system of responsibility of the administrators and other bodies of the company, it is the duty of this to indemnify the damages caused to the investors of the capital market, since the former are mere instruments of manifestation of their will